Bio-oil from Oil Palm Shell Pyrolysis as Renewable Energy: A Review - Joko Pitoyo; Totok Eka Suharto; Siti Jamilatun (CHEMICA: Jurnal Teknik Kimia, 2022)
Oil palm shell (OPS) is biomass with high carbon and hydrogen content, so it has the potential to produce renewable energy through the thermochemical method. Pyrolysis is a relatively inexpensive thermochemical method that continuously converts biomass into valuable gas, bio-oil, and char products. Bio-oil is used directly to fuel boilers and furnaces or to produce fuel oil. This article reviews the pyrolysis process of biomass from oil palm shells, discussing the operating parameters that influence the pyrolysis process and the method of upgrading bio-oil. This review shows a relationship between biomass composition (cellulose, hemicellulose, and lignin) and bio-oil yield. The water content in the raw material needs to be controlled at around 10%. The optimum particle size is closely related to the biomass's natural structure and reactor type. The higher the ash and fixed carbon content, the lower the bio-oil yield. The optimum temperature for pyrolysis is between 450-550 ºC. A high heating rate will increase the decomposition of biomass into bio-oil. Particle size and reactor type strongly influence feed rate, residence time, and reaction time. A fluidized bed reactor gives the highest bio-oil yield. Using plastic in co-pyrolysis and catalyst increases the heating value and decreases the oxygenated content.